N. elongata produces type IV pili that mediate interspecies gene transfer with N. gonorrhoeae. - Dustin L Higashi; Nicolas Biais; Nathan J Weyand; Al Agellon; Jennifer L Sisko; Lewis M Brown; Magdalene So (PLoS ONE)
The genus Neisseria contains at least eight commensal and two pathogenic species. According to the Neisseria phylogenetic tree, commensals are basal to the pathogens. N. elongata, which is at the opposite end of the tree from N. gonorrhoeae, has been observed to be fimbriated, and these fimbriae are correlated with genetic competence in this organism. We tested the hypothesis that the fimbriae of N. elongata are Type IV pili (Tfp), and that Tfp functions in genetic competence. We provide evidence that the N. elongata fimbriae are indeed Tfp. Tfp, as well as the DNA Uptake Sequence (DUS), greatly enhance N. elongata DNA transformation. Tfp allows N. elongata to make intimate contact with N. gonorrhoeae and to mediate the transfer of antibiotic resistance markers between these two species. We conclude that Tfp functional for genetic competence is a trait of a commensal member of the Neisseria genus. Our findings provide a mechanism for the horizontal gene transfer that has been observed among Neisseria species.